Wavelet investigation of Soret and Dufour effects on stagnation point fluid flow in two dimensions with variable thermal conductivity and diffusivity. (21st August 2019) - Hamid, Muhammad; Usman, Muhammad; Haq, Rizwan Ul
Abstract: The current analysis is devoted to observing the influence of Soret and Dufour effects on stagnation point fluid flow in two dimensions. The buoyancy effects, variable thermal conductivity and diffusivity are also considered in our study. The governing equations of flow are reduced to a nonlinear ordinary differential equation system via a suitable transformation technique. The numerical simulation is performed by means of a new algorithm based on the Chebyshev wavelet method (MCWM). A detailed assessment of outcomes obtained by MCWM with fourth-order Runge–Kutta technique is available to support our wavelet-based solution. The significant properties and effects of various physical parameters are presented graphically. It is noted that an increase in the values of magnetic parameters cause a decrease in the velocity profile for the assisting case while the behavior of velocity is the opposite for the opposing case. The effects of Soret and Dufour enhanced the temperature and concentration, respectively. The comparison and convergence analysis indicate that the proposed algorithm is an efficient tool and could be extended for other complex nature models in engineering and physics.